Working On Vocabulary in Native Language Classes - Buvajonova Mohirakhan Usmonali qizi (Zien Journals, 2021)
The main purpose of mother tongue teaching is the role of language in society determined. Language is the means by which the speaker conveys his thoughts through language, and the listener represents the idea realized through the means of language. The following article looks into the methods of working on vocabulary in elementary native language classes
Keywords: Mother tongue; vocabulary; speech; comprehension